Walking alone milestone combined reading-frame rule improves early prediction of Duchenne muscular dystrophy - Ma, Yan-li; Zhang, Wei-hua; Chen, Guo-hong; Song, Li-fang; Wang, Yuan; Yuan, Rui-li; Wang, Ying; Cheng, Xiu-yong (Frontiers in Pediatrics, 2022)
ABSTRACT OBJECTIVE: To explore the potential of walking alone milestone combined reading-frame rule to improve the early diagnosis of Duchenne muscular dystrophy (DMD). METHOD: To retrospectively describe the genotype and phenotype of Duchenne and Becker muscular dystrophies (BMD) patients with deletions and duplicates in the dystrophin gene. The sensitivity and specificity of the reading frame rule were calculated and compared to that of the combined reading frame rule and walking alone milestone. The diagnostic coincidence rate of two different methods was analyzed. RESULT: 169 male DMD/BMD patients were enrolled, including 17 cases of BMD and 152 cases of DMD. The diagnostic coincidence rate, diagnostic sensitivity, and specificity of the reading-frame rule for DMD/BMD were 85.2%, 86.8%, and 70.59%, respectively. The sensitivity and specificity of the reading frame principle combined with the walking alone milestone for DMD/BMD were 96.05% and 70.59%, respectively. The diagnostic coincidence rate increased to 93.49%, significantly different from that predicted by reading- frame rule (P<0.05). Conclusion: The reading-frame rule combined with the walking alone milestone significantly improved the early diagnosis rate of DMD.